Profile of Urine Sediment Examination Results Among Tailors in Sidorejo Village, Comal Subdistrict, Pemalang Regency - Juliyanti, Silviana; Riyanto, Agus (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Urine sediment examination is used to detect abnormalities in the kidneys and urinary tract, as well as the severity of disease. Morning urine is preferred because it contains a higher concentration of sediments. For workers engaged in prolonged static activities, such as tailors, this test is important to identify potential health risks associated with occupational habits and unhealthy environments. Tailoring requires sitting for long periods to meet customer demands, increasing the risk of urinary tract stones (urolithiasis). This study aimed to describe the results of urine sediment examination among tailors in Sidorejo Village, Comal Subdistrict, Pemalang Regency. Method: This descriptive study employed purposive sampling, with 30 respondents providing urine samples for sediment analysis. Result: Of the 30 urine samples, 2 showed erythrocytes, 2 showed leukocytes, 27 showed squamous epithelial cells, 9 showed transitional epithelial cells, 14 showed calcium oxalate crystals, and 12 showed uric acid crystals. Conclusion: Urine sediment examination among tailors in Sidorejo Village revealed the presence of erythrocytes, leukocytes, squamous epithelial cells, transitional epithelial cells, calcium oxalate crystals, and uric acid crystals. This highlights the importance of regular urine sediment testing for workers with static activities such as tailoring, as it may help in the early detection of potential health problems caused by occupational habits and poor working conditions.